KONSUMSI SAYUR DAN BUAH DENGAN KEJADIAN OBESITAS PADA REMAJA DI SMA NEGERI 1 MAMUJU - Yuliah Yuliah; Adriyani Adam; Muh. Hasyim (Jurnal Kesehatan Manarang, 2017)
Vegetables and fruits consumption in adolescents is very important and contains many nutrients such as vitamins, minerals and fiber in achieving a healthy lifestyle with balanced nutrition. Some vitamins and minerals contained in vegetables and fruits have antioxidant functions that can reduce the incidence of non-communicable diseases associated with nutrition, as a result of overweight or malnutrition. Vegetables and fruits are also rich in vitamins and minerals that play a role in the metabolic system in the body including energy metabolism. The aim of this study is to analysis the relationship vegetable and fruit consumption with the incidence of obesity in SMA Negeri 1 Mamuju 2016. Design of this study is analytic research with cros sectional approach. Samples are 280 students of SMU Negeri 1 Kabupaten Mamuju with sampling method by systematic random sampling. The results of the research for the consumption of vegetable category is quite as many as 114 people (40.7%) and less vegetable consumption of 166 people (59.3%). Chi-square test results obtained p > ​​0.05, there is no relationship between vegetable consumption with the incidence of obesity. For the consumption of enough fruits as many as 92 people (32.9%) and less fruit consumption of 188 people (67.1%). Chi-square test results obtained p value > 0.05 , there is no relationship between fruit consumption with the incidence of obesity. Suggestions in this study is the need for intensive information about the importance of healthy lifestyles and balanced nutrition for adolescents to achieve the ideal body weight.